2012
DOI: 10.1159/000334142
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of Blood Volume Measurements during Hemodialysis

Abstract: Devices that continuously measure relative blood volume (RBV) changes during hemodialysis (HD) are increasingly used for the prevention of dialysis hypotension and fine-tuning of dry weight. However, RBV measurements are subject to various limitations. First, RBV devices provide information on relative blood volume changes but not on absolute blood volume. Since blood volume varies with the hydration status, identical reductions of RBV may result in very different absolute blood volumes at the end of HD. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 52 publications
4
59
0
1
Order By: Relevance
“…Unfortunately, available data precluded study of the effects of dialysis sodium concentration and dialysate temperature, both of which may also affect IDH (21). Furthermore, prior studies indicate that fluid status with respect to extracellular euvolemia may be an important determinant in IDH (22,23). In time, emerging technologies may enable real-time consideration of volume status to ameliorate IDH and downstream CV events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, available data precluded study of the effects of dialysis sodium concentration and dialysate temperature, both of which may also affect IDH (21). Furthermore, prior studies indicate that fluid status with respect to extracellular euvolemia may be an important determinant in IDH (22,23). In time, emerging technologies may enable real-time consideration of volume status to ameliorate IDH and downstream CV events.…”
Section: Discussionmentioning
confidence: 99%
“…To date, analyses regarding the effect of such technologies have yielded mixed findings, possibly based on differences in protocolized responses to IDH. Further study is needed to optimally translate data on extracellular volume into clinical responses (23).…”
Section: Discussionmentioning
confidence: 99%
“…FO is one of many factors influencing this relationship. It has often been reported that flat RBV curves are a sign of excessive FO [6,8,9,11]. According to Guyton and Hall [24], about two thirds of FO contribute to the interstitial space, and the remaining third contributes to the blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…to reduce intradialytic morbid events by controlling the ultrafiltration rate (UFR). Recently however, its utility for fluid status assessment has come more into focus [8,9,10,11]. Some authors have proposed to categorize patients' fluid status by the shape of their intradialytic blood volume reduction or postdialytic volume rebound curves [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…These devices heighten the awareness and decision-making data that clinicians use to reduce volume-related hospitalization and urgent dialysis therapy (6).…”
Section: Opportunities and Challengesmentioning
confidence: 99%